Selected issues on the law of trust: a comparative study of judicial attitudes in Malaysia and United Kingdom / Sarah Rosley … [et al.] - Rosley, Sarah; Nazri, Nur Amalina; Ramlan, Noor Amalina; Ahmad Yossry, Nur Aisya (2014)
This research paper outline on the judicial application of the trust mechanism in avoiding the doctrine of privity. It first identifies the issue and the situation in Malaysia and United Kingdom with reference to relevant cases. It also includes the approaches taken by the court in Malaysia and United Kingdom in deciding the cases related to doctrine of privity by using the trust mechanism. This research paper also outline on the differences based on legislation between the charitable trust in Malaysia and United Kingdom. It also includes the differences in Malaysia and United Kingdom on the doctrine of cy-pres as well as the taxation of trust. For this research paper, appropriate recommendation for charitable trust and doctrine of privity in Malaysia has been proposed and the overall conclusion are provided in Chapter 5 in the paper.